What does tooth enamel tell us of lived lives?: A study of the neonatal line and other accentuated lines in human deciduous enamel - Hurnanen, Jaana (fi=Turun yliopisto|en=University of Turku|, 2023)
The purpose of this study was to investigate the varying width and structure of the neonatal line (NNL) and the occurrence of other accentuated lines (ALs) and their association with known early life events. The NNL was identified and the effect of the mode and duration of delivery on the NNL width was assessed (Study I). The effect of tooth type and perinatal factors on the formation of the staircase (Sc) pattern in the NNL was evaluated (Study II). The probabilities were analysed for how likely certain life events are determinants of ALs (Study III). The 129 investigated Finnish Deciduous Tooth (FDT) collection teeth are part of a longitudinal population-based follow-up study, the Finnish Family Competence study. The NNL was detected, and the width measured using a transmitted light microscope (Study I) and the Sc pattern was investigated using polarisation (Study II). ALs were identified from polarisation light microscope tile scan images and compared with known postnatal life events (Study III). The NNL was identified, and width was inversely associated with the duration of delivery (p=0.0097). The mode of delivery had no effect on the NNL width (Study I). The Sc pattern was highly related to the tooth type (p<0.0001) and more present in the in the middle third of the vertical crown wall enamel (p<0.0001). Mode, duration of delivery or pain medication did not affect the NNL Sc pattern formation (Study II). 56% of canine ALs were located in the middle third of the crown height. Vaccinations and/or ear infections were not regular determinants for ALs (Study III). The neonatal line exists in practically all deciduous teeth. Its width is inversely interrelated with the duration of delivery. The neonatal line structure and the occurrence of accentuated lines are dependent on their topographical location: in the mid-height of the tooth crown the ameloblast susceptibility seems stronger along the enamel forming front. The most frequently appearing disease, ear infection, and vaccinations are not likely to always engender accentuated lines in the FDT collection samples.